2011
DOI: 10.1038/npp.2011.258
|View full text |Cite
|
Sign up to set email alerts
|

α- and β-Adrenergic Receptors Differentially Modulate the Emission of Spontaneous and Amphetamine-Induced 50-kHz Ultrasonic Vocalizations in Adult Rats

Abstract: Amphetamine (AMPH) increases adult rat 50-kHz ultrasonic vocalizations, preferentially promoting frequency-modulated (FM) calls that have been proposed to reflect positive affect. The main objective of this study was to investigate a possible noradrenergic contribution to AMPH-induced calling. Adult male Long-Evans rats were tested with AMPH (1 mg/kg intraperitoneal) or saline combined with various systemic pretreatments: clonidine (α2 adrenergic agonist), prazosin (α1 antagonist), atipamezole (α2 antagonist),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 113 publications
5
91
3
Order By: Relevance
“…Indeed, as negotiating close-quarter contact, which occurs when one rat rolling over onto its back is attacked by another, appears to involve more sophisticated interanimal coordination than other tactics not involved in such close-quarter action (Pellis and Pellis, 1987;Bell et al, 2009), a reduced ability to communicate could diminish the use of such tactics during play. Given the diversity of 50 kHz calls (Wright et al, 2010(Wright et al, , 2012, a detailed analysis of the temporal structure of when different calls are emitted during the course of the momentto-moment maneuvers performed during play may shed light on such deficits in communication. These communicatory effects of VPA need not be exclusive from the effects on the motivation and reward systems for social contact.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, as negotiating close-quarter contact, which occurs when one rat rolling over onto its back is attacked by another, appears to involve more sophisticated interanimal coordination than other tactics not involved in such close-quarter action (Pellis and Pellis, 1987;Bell et al, 2009), a reduced ability to communicate could diminish the use of such tactics during play. Given the diversity of 50 kHz calls (Wright et al, 2010(Wright et al, , 2012, a detailed analysis of the temporal structure of when different calls are emitted during the course of the momentto-moment maneuvers performed during play may shed light on such deficits in communication. These communicatory effects of VPA need not be exclusive from the effects on the motivation and reward systems for social contact.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has demonstrated a significant contribution of the noradrenergic system to acoustic variables; for example, call rate is increased with noradrenergic system treatments in adult rats [78]. However, the effect on acoustic parameters including intensity, bandwidth and peak frequency are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[51] Given this, it is possible that some aspects of the observed vocalization deficits are related to norepinephrine loss in addition to dopamine loss. It has been demonstrated that selectively agonizing or antagonizing noradrenergic receptors results in differential alterations to call rate in profile,[52] though the contribution of norepinephrine to other acoustic parameters such as intensity, bandwidth and peak frequency are unknown. In addition, preliminary work in our lab indicates that systemic injections of the noradrenergic neurotoxin DSP-4 results in acute, transient alterations to acoustic parameters of ultrasonic vocalizations such as intensity and bandwidth (unpublished).…”
Section: Discussionmentioning
confidence: 99%